Cystic fibrosis treatment; small molecule modulators vs genetic therapy - Salma Aly Elmallah; Raafat Soliman (Academy Publishing Center, 2022)
Cystic fibrosis, CF, is one of the most common life-shortening genetic diseases among Caucasian population. It is a recessive genetic disease that is mainly caused by different types of mutations affecting the gene encoding for the cystic fibrosis transmembrane conductance regulator, CFTR, protein. CFTR is a multifunctional protein found in multiple organs in the human body, acting mainly as a trans-epithelial channel which regulates the flow of chloride and bicarbonate ions across epithelial membranes leading to the formation of a thin slippery mucous layer. A malfunctioning CFTR protein would lead to the accumulation of a thick viscous mucous layer blocking pancreatic ducts, intestines and airways which is the primary reason of death. Treatment of cystic fibrosis was mainly addressing the symptoms to overcome the complications of the disease such as pneumonia, lung infections, pancreatitis, maldigestion and infertility. Since the early 2010's, the development of an actual therapy has reached great milestones including small molecule modulators and genetic therapy. Small molecule therapy depends on the development of small pharmacological agents that can bind to the mutated CFTR protein restoring its function. Pharmacological agents can act through different mechanisms and be mainly classified to; correctors and potentiators. On the other hand, gene-editing techniques are evolving showing very promising results. Gene therapy entails the relocation of a proper copy of the CFTR gene in the aim of expressing a functional CFTR protein. In this review article, small molecule and genetic therapies will be discussed including their development, benefits and limitations.